Editorial: Arts Education in a More-Than-Human World - Ylirisku, Henrika; Slotte Dufva, Tomi; Snellman, Mikko (Aalto-yliopisto, 2025)
"Once upon a time, in a world where change danced on the horizon like leaves in the wind, there were art teachers, artist-pedagogues, artists, and art educational researchers, who read themselves into the posthumanist theories.
Or maybe they engaged with the key ideas of these theories through their colleagues, or from random YouTube videos.
Or maybe they ended up following the call of vital materialities, or became attracted by encounters with other-than-human species (clicks of cameras capturing fleeting moments, water droplets dotting on snow, or the whispers of limpets clinging to rocky shores).
In any case, something in the world made them think differently their understandings of learning, pedagogies, art practices and research.
This resulted in creative experimentation, rigorous rethinking of existing practices, and negotiating ethical responses to the messy, complex entanglements in the more-than-human worlds."